Effects of Anadara granosa shell combined with Sardinella longiceps oil on oesteoblast proliferation in bone defect healing process - Rima Parwati Sari; Eddy Hermanto; Dinda Divilia; Indra Candra; Wisnu Kuncoro; Tantri Liswanti (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Alveolar bone damage is the most common case in dentistry. One way to fix the bone damage is by using bone graft. Anadara granosa shell is a potential bone substitute since it is rich in calcium which can be processed into hydroxyapatite. The addition of Sardinella longiceps oil rich in omega-3 can modulate inflammation, thus accelerating the healing process. Purpose: This study aimed to determine effects of application of Anadara granosa shell combined with Sardinella longiceps oil on osteoblast proliferation in the healing process of bone defects. Method: The subjects were 32 male rats type Wistar divided into 4 groups (n = 8). Making defect was performed on the right bone of the femurs with a half of the diameter of round Mcisinger® Germany bur sized 18. The first group (K) is a negative control group that was not given anything. The second group (AG) was given Anadara granosa pasta. The third group (AM10) was given Anadara granosa pasta combined with 10% Sardinella longiceps oil. And, the fourth group (AM30) was given Anadara granosa pasta combined with 30% Sardinella longiceps oil. Next, preparations and animal euthanasia were performed on the 7th day after the treatment. The number of osteoblasts then was measured after making preparations for HPA with Hematoxylin eosin staining (HE). Afterward, tabulation of data followed by statistical analysis of Anova and HSD Tukey was carried out. Result: The average number of osteoblasts in Groups K, AG, AM10, and AM30 was 19.00, 34.63, 33.50, and 38.50. The results of Anova test showed a significant difference (p<0.05). Similarly, the results of Tukey-HSD test also showed significant differences (p<0.05) between Group K and all other groups (AG, AM10, and AM30). Nevertheless, there were no significant differences between Group AG and Groups AM10 and AM30, as well as between Group AM10 and Group AM30. Conclusion: The application of the combination of Anadara granosa shell and Sardinella longiceps oil can not increase the proliferation of osteoblasts in the healing process of bone defects.